Quality of Labor Analgesia with Dural Puncture Epidural versus Standard Epidural Technique in Obese Parturients: A Double-blind Randomized Controlled Study. (14th February 2022) - Tan, Hon Sen; Reed, Sydney E.; Mehdiratta, Jennifer E.; Diomede, Olga I.; Landreth, Riley; Gatta, Luke A.; Weikel, Daniel; Habib, Ashraf S.
Abstract : Background: The dural puncture epidural technique may improve analgesia quality by confirming midline placement and increasing intrathecal translocation of epidural medications. This would be advantageous in obese parturients with increased risk of block failure. This study hypothesizes that quality of labor analgesia will be improved with dural puncture epidural compared to standard epidural technique in obese parturients. Methods: Term parturients with body mass index greater than or equal to 35 kg · m –2, cervical dilation of 2 to 7 cm, and pain score of greater than 4 (where 0 indicates no pain and 10 indicates the worst pain imaginable) were randomized to dural puncture epidural (using 25-gauge Whitacre needle) or standard epidural techniques. Analgesia was initiated with 15 ml of 0.1% ropivacaine with 2 µg · ml –1 fentanyl, followed by programed intermittent boluses (6 ml every 45 min), with patient-controlled epidural analgesia. Parturients were blinded to group allocation. The data were collected by blinded investigators every 3 min for 30 min and then every 2 h until delivery. The primary outcome was a composite of (1) asymmetrical block, (2) epidural top-ups, (3) catheter adjustments, (4) catheter replacement, and (5) failed conversion to regional anesthesia for cesarean delivery. Secondary outcomes included time to a pain score of 1 or less, sensory levels at 30 min, motor block, maximum pain score, patient-controlled epidural analgesia use, epidural medication consumption, duration of second stage of labor, delivery mode, fetal heart tones changes, Apgar scores, maternal adverse events, and satisfaction with analgesia. Results: Of 141 parturients randomized, 66 per group were included in the analysis. There were no statistically or clinically significant differences between the dural puncture epidural and standard epidural groups in the primary composite outcome (34 of 66, 52% vs . 32 of 66, 49%; odds ratio, 1.1 [0.5 to 2.4]; P = 0.766), its individual components, or any of the secondary outcomes. Conclusions: A lack of differences in quality of labor analgesia between the two techniques in this study does not support routine use of the dural puncture epidural technique in obese parturients. Abstract : A total of 132 term parturients with a body mass index of 35 kg · m –2 or greater were randomized to either a dural puncture epidural using a 25-gauge Whitacre needle or a standardized epidural technique. This was followed, in both groups, by maintenance with programed intermittent boluses and patient-controlled epidural analgesia. The primary outcome was a composite of five outcomes indicating lower quality of labor analgesia. There was no meaningful difference between the two groups (52 vs. 49%; absolute risk difference, 3.0%; 95% CI, –14.0 to 20.1%) in the primary outcome or the secondary outcomes assessed. The study excludes a large benefit for dural puncture epidural in improving labor analgesia in obese parturients, although CI ranges for the primary outcome were wide and do not fully exclude the potential for a clinically meaningful effect.